Green Synthesis of Carbon Nitride‐Based Conjugated Copolymer for Efficient Photocatalytic Degradation of Tetracycline. Issue 18 (23rd March 2022) - Hu, Zhen; Liu, Ning; He, Panpan; Bai, Huiying; Hao, Liang; Min, Jiakang; Fan, Zifen; Chen, Bingyu; Niu, Ran; Gong, Jiang
Abstract: Upcycling waste plastics into advanced semiconductor photocatalysts provides a new strategy to reasonably and economically solve the huge amount of waste plastics, which remains challenging. Herein, a carbon nitride‐based donor–acceptor (D–A) conjugated copolymer by copolymerization of dicyandiamide and terephthalic acid from discarded polyethylene terephthalate (PET) using Zn(OH)2 as catalyst and template at 360–440 °C is synthesized. The morphology and structure of the conjugated copolymer are well regulated by the calcination temperature. The resultant conjugated copolymer exhibits merits of high light absorption and low electron–hole recombination probability. Consequently, it works excellently in the persulfate‐based advanced oxidation process for visible light‐driven photocatalytic degradation of tetracycline. The kinetic constant (3.4 × 10 −2 min −1 ) is 40.5 and 2.3 times that of the conjugated copolymer system and persulfate system, respectively. Furthermore, the reactive species (including OH, SO4 −, O2 −, 1 O2, and h + ) and degradation intermediates of tetracycline are analyzed to expound its degradation process. This work not only pioneers design guidelines on upcycling of waste plastics in a sustainable manner, but also provides a facile strategy to synthesize carbon nitride‐based D–A conjugated copolymers for the efficient activation of persulfate‐based advanced oxidation process in wastewater treatment. Abstract : A novel C3 N4 ‐based donor–acceptor conjugated copolymer with controlled structures is synthesized by copolymerization of dicyandiamide and terephthalic acid from discarded polyethylene terephthalate using Zn(OH)2 at 360–440 °C. The conjugated copolymer exhibits merits of high light absorption and low electron–hole recombination probability, and works excellently in the persulfate‐based advanced oxidation process for visible light‐driven photocatalytic degradation of tetracycline.